Experimental analysis of Li-ion cell fire and its spreading - Boey, Delson Bo Jie (Nanyang Technological University, 2023)
The Lithium-ion battery (LIB) chain was expected to grow by over 30% annually, with a market size of 700GWh in 2022, to 4.7TWh in 2030, which is valued over $400 billion [1]. This rapid growth comes amid rising demands for countries and manufacturers to produce greener, more sustainable products to slow down global warming. Over 90% of its demand would go towards Electric Vehicles (EVs) as government regulations and manufacturers adopt more stringent emission targets and goals [2]. In our daily lives, we interact with at least one electronic device which is powered by LIBs, that is – our mobile phones. Almost every large automobile company is making the switch to go hybrid or full electric within ten to fifteen years’ time, with Jaguar making plans to make the switch to a full electric line-up by 2025 [3]. Manufacturers compete to produce more energy storage systems and devices for the mass market, while ensuring the safety of the products. However, due to the long and arduous process of producing safe and reliable LIBs, the costs to purchase them are higher. This has led to the search for cheaper alternatives by companies to lower the cost of production for their products. Budget friendlier PMD companies turn to unbranded batteries, which are almost a third of the price of branded ones such as Samsung SDI and BYD. The elastic demand for PMDs make buyers more attracted to lower prices, unaware of the reason of it [4]. In 2021 alone, there were 32 fires involving PMDs , of which 24 were uncertified [5]. The increase in number of house fires in Singapore has led the government to introduce regulatory controls requiring all Personal Mobility Devices (PMDs) to be UL2272 certified being sold or used in the country [6]. In December 2022, a 20 year old died of extensive burns to 95% of his body when his PMD burst into flames in the lift [7]. This highlights the dangers of LIBs which taken the lives of the innocent. This project aimed to understand the conditions required for LIBs to explode. This requires the designing and testing of the experimental setup, then varying charging and heating temperatures applied to the LIB until it explodes. This project also studied the spreading effects of LIBs via Thermal Runaway (TR). The experiment can progress into finding solutions to prevent the LIBs from failing. One such solution would be to install Cell Fire Extinguishers (CFE), which are tiny fire extinguishers. This would be done by emitting fire retardant on the CFE to cool or extinguish the fire before the next LIB explodes via the process of TR.